Overexpression of thioredoxin h leads to enhanced activity of starch debranching enzyme (pullulanase) in barley grain - Cho, Myeong-Je (The National Academy of Sciences, 1999)
Biochemically active wheat thioredoxin h has been overexpressed in the endosperm of transgenic barley grain. Two DNA constructs containing the wheat thioredoxin h gene (wtrxh) were used for transformation; each contained wtrxh fused to an endosperm-specific B(1)-hordein promoter either with or without a signal peptide sequence for targeting to the protein body. Twenty-two stable, independently transformed regenerable lines were obtained by selecting with the herbicide bialaphos to test for the presence of the bar herbicide resistance gene on a cotransformed plasmid; all were positive for this gene. The presence of wtrxh was confirmed in 20 lines by PCR analysis, and the identity and level of expression of wheat thioredoxin h was assessed by immunoblots. Although levels varied among the different transgenic events, wheat thioredoxin h was consistently highly expressed (up to 30-fold) in the transgenic grain. Transgenic lines transformed with the B(1)-hordein promoter with a signal peptide sequence produced a higher level of wheat thioredoxin h on average than those without a signal sequence. The overexpression of thioredoxin h in the endosperm of germinated grain effected up to a 4-fold increase in the activity of the starch debranching enzyme, pullulanase (limit dextrinase), the enzyme that specifically cleaves α-1,6 linkages in starch. These results raise the question of how thioredoxin h enhances the activity of pullulanase because it was found that the inhibitor had become inactive before the enzyme showed appreciable activity.